Comparison of the efficacy and safety of endoscopic ultrasound‐guided choledochoduodenostomy and hepaticogastrostomy for malignant distal biliary obstruction: Multicenter, randomized, clinical trial. Issue 5 (29th May 2019) - Minaga, Kosuke; Ogura, Takeshi; Shiomi, Hideyuki; Imai, Hajime; Hoki, Noriyuki; Takenaka, Mamoru; Nishikiori, Hidefumi; Yamashita, Yukitaka; Hisa, Takeshi; Kato, Hironari; Kamada, Hideki; Okuda, Atsushi; et al.
Abstract : Background and Aim: Endoscopic ultrasound‐guided biliary drainage (EUS‐BD) can be carried out by two different approaches: choledochoduodenostomy (CDS) and hepaticogastrostomy (HGS). We compared the efficacy and safety of these approaches in malignant distal biliary obstruction (MDBO) patients using a prospective, randomized clinical trial. Methods: Patients with malignant distal biliary obstruction after failed endoscopic retrograde cholangiopancreatography were randomly selected for either CDS or HGS. The procedures were carried out at nine tertiary centers from September 2013 to March 2016. Primary endpoint was technical success rate, and the noninferiority of HGS to CDS was examined with a one‐sided significance level of 5%, where the noninferiority margin was set at 15%. Secondary endpoints were clinical success, adverse events (AE), stent patency, survival time, and overall technical success including alternative EUS‐BD procedures. Results: Forty‐seven patients (HGS, 24; CDS, 23) were enrolled. Technical success rates were 87.5% and 82.6% in the HGS and CDS groups, respectively, where the lower limit of the 90% confidence interval of the risk difference was −12.2% ( P  =   0.0278). Clinical success rates were 100% and 94.7% in the HGS and CDS groups, respectively ( P  =   0.475). Overall AE rate, stent patency, and survival time did not differ between the groups. Overall technical success rates were 100% and 95.7% in the HGS and CDS groups, respectively ( P  =   0.983). Conclusions: This study suggests that HGS is not inferior to CDS in terms of technical success. When one procedure is particularly challenging, readily switching to the other could increase technical success.